Enhancing Energy Efficiency & Productivity With Solar Cells For Wifi Operations In Mining Are-as Pt Antareja Mahada Makmur Jobsite Mifa Ber-saudara (2024) - Rahmad Dananjaya; Alfons Weldam; Anjasmara Biopatra; Haris Batubara (Green Publisher Indonesia, 2024)
This improvement aims to evaluate the effectiveness of the use of solar cell systems in improving energy efficiency and WiFi network productivity in coal mining environments. The research method involves the installation of solar cell systems and the measurement of energy performance and productivity before and after implementation. The implementation of solar cell systems on WiFi networks in mining environments can improve energy efficiency and productivity. This study aims to analyze the influence of the implementation of solar cell systems on fossil energy use and environmental impact. The results show that the implementation of the solar cell system can reduce the use of fossil energy by 75% and reduce greenhouse gas emissions by 60%. The implementation of the solar cell system can also increase productivity by 25%. Therefore, the implementation of a solar cell system on a WiFi network in a mining operational environment is highly recommended. The results showed a significant improvement in the energy efficiency and stability of the WiFi network, which had a positive impact on operational productivity. The results of the study show that the use of solar cells can significantly reduce the consumption of electricity/fossil energy, as well as increase the availability of WiFi networks to support PT AMM's operational support activities. The implication of this study is the great potential of the use of solar energy to improve operational efficiency and reduce environmental impact.